Efficiency evaluation of a natural material for removal of cationic oxazine and anionic azo dyes from aqueous solutions - Boudaoud Asma; Ad Chifaa; Djedid Mebrouk; Benalia Mokhtar; Guermit Mounira; Amel Soltani (Hemijska Industrija)
The current work involves studying the adsorption process of brilliant cresyl blue (BCB) and methyl orange (MeO) dyes using local pumpkin seed husks (LPSH). The LPSH adsorbent was analysed by using Fourier transform infrared spectroscopy, scanning electron microscopy with energy dispersive x-ray spectroscopy, X-ray diffraction and Brunauer-Emmett-Teller analyses. The descriptive analysis of the morphology of LPSH revealed a heterogeneous surface, while the structural analysis showed the presence of functional groups typical of lignocellulosic structures and it was confirmed that the mesoporous surface of the adsorbent had a specific surface area of ~1.53 m2 g-1. The adsorption isotherm studies suggested that the Langmuir model best described the adsorption of MeO, while the Freundlich model is more suitable for describing the adsorption of BCB. According to the thermodynamic analyses, the adsorption of BCB was exothermic and spontaneous, whereas the adsorption of MeO was endothermic and non-spontaneous. The results of evaluating the efficiency of the LPSH adsorbent showed that the maximum adsorption capacities are ~81 mg g-1 for the BCB dye and ~8.2 mg g-1 for the MeO dye.